Developing Scrabble Wall for Students’ Vocabulary Learning - Sarah Fauziah; Fitri Hilmiyati; Siti Sa'diah (Jurnal Pendidikan, 2023)
Mastering vocabulary could be one of the keys to be successful in learning English. Teaching by using a certain game could be an interesting way to increase students’ vocabulary. The aim of this study is to create a scrabble wall to help students improve their vocabulary. This study employed the research and development method, as well as the ADDIE Model's theory, which is divided into five stages: analysis, design, development, implementation, and evaluation. Interviews, exams, and expert validation checklists were used as study instruments. This study used 25 students as a sample of product implementation among eleventh-grade students of SMA Putra Juang Cianjur. Data were gathered from student interviews, test results (Pre-test and Post-test), teacher replies, and expert validation results. The data analysis revealed that the product was both good and valid. The scrabble wall can be used as a means to teach English, particularly vocabulary. The scrabble wall is helpful for students as well. It may be concluded that the use of scrabble wall can enhance students’ vocabulary mastery.